Molecular heterosis of prion protein beta-oligomers. A potential mechanism of human resistance to disease. - Tahiri-Alaoui, A; Sim, V; Caughey, B; James, W (2006)
The gene encoding prion protein is polymorphic in human populations, with over 40% of native Europeans, for example, being heterozygous for the Met-129 and Val-129 alleles. The polymorphism affects both the incidence and the clinical presentation of a range of prion diseases, with heterozygotes generally showing the highest levels of resistance. It has been suggested that an earlier epidemic of prion diseases exerted balancing selection on the two alleles, and we have previously demonstrated that the two encoded proteins have potentially compensating tendencies to form amyloid and soluble beta-oligomers, respectively, in vitro. More strikingly, here we demonstrate that mixed oligomers, composed of both allelic forms, show an extreme sluggishness in converting to amyloid in comparison with oligomers homogenous for either allele. It may be that this example of molecular heterosis in vitro provides the basis for maintenance of the polymorphism in the population and that beta-oligomers represent a form of PrP sequestered from pathogenic amyloid formation in vivo.